Interaction of Echicetin with a High Affinity Thrombin Binding Site on Platelet Glycoprotein GPIb - Peng, Manling; Emig, Frances A; Mao, Ahua; Lu, Weiqi; Kirby, Edward P; Niewiarowski, Stefan; Kowalska, M Anna (Thrombosis and Haemostasis, 1995)
Echicetin, a protein isolated from Echis carinatus snake venom, inhibited platelet aggregation and secretion induced by low concentrations of thrombin (<0.2 U/ml), by binding to platelet glycoprotein lb (GPIb). The inhibition was not observed when the platelets were stimulated with higher concentrations of thrombin (>0.2 U/ml). Echicetin competed with thrombin for binding to the high affinity site on GPIb. Thrombin also inhibited 50% of the binding of 125I-echicetin to the platelets.